Investigation on determinants of saving behavior among employees in Malaysia / Azreenabila Norliza - Norliza, Azreenabila (Faculty of Business and Management, 2020)
This research is to investigate the relationships between financial knowledge, financial planning and retirement planning with saving behavior. The sample in this research is to investigate employees in Petronas, Malaysia which involved 150 totals of respondents were chosen through purposive sampling of employees that working in Petronas, Malaysia. In order to obtain the result, frequency distribution, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis were conducted in the analysis part. The findings recommend that the financial knowledge and retirement planning has significant relationships with saving behavior. Financial knowledge is found as the most influenced predictor towards saving behavior followed by financial planning and retirement planning. These finding could contribute to the body of knowledge by identifying determinants of saving behavior among employees in Petronas. Theory of planned behavior is used to underpin a proposed theoretical framework. The study shows the absence of financial knowledge, financial planning, retirement planning will enhance the level of saving behavior among employees in Petronas.